2012
DOI: 10.1007/s10695-011-9600-2
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic adjustments of Dentex dentex to prolonged starvation and refeeding

Abstract: The particular metabolic strategies of the common dentex (Dentex dentex) to face a period of prolonged starvation and subsequent refeeding were assessed. Plasma metabolites, endogenous reserves, and the activity of key enzymes of intermediary metabolism in liver, white muscle, and heart were evaluated. Plasma glucose, total lipid, triglycerides, total-, HDL- and LDL-cholesterol, and protein levels, liver, and white muscle glycogen, and perivisceral, and muscle fat were significantly reduced by starvation, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
54
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 63 publications
9
54
0
1
Order By: Relevance
“…Pérez-Jimenez et al (2007) have demonstrated that starvation can decrease in plasma total triglyceride and cholesterol levels during food deprivation periods. Numerous studies have reported a reduction in plasma triglyceride and cholesterol levels during starvation (Hung et al 1997;Polakof et al 2006;Pérez-Jiménez et al 2007;Costas et al 2011;Furné et al 2012;Perez-Jimenez et al 2012). The outcome of the present results and other studies revealed that there will be a decline in glycogen reserves, during the food deprivation period followed by decreased plasma glucose level.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Pérez-Jimenez et al (2007) have demonstrated that starvation can decrease in plasma total triglyceride and cholesterol levels during food deprivation periods. Numerous studies have reported a reduction in plasma triglyceride and cholesterol levels during starvation (Hung et al 1997;Polakof et al 2006;Pérez-Jiménez et al 2007;Costas et al 2011;Furné et al 2012;Perez-Jimenez et al 2012). The outcome of the present results and other studies revealed that there will be a decline in glycogen reserves, during the food deprivation period followed by decreased plasma glucose level.…”
Section: Discussionsupporting
confidence: 77%
“…Similar to the results of present study, Hung et al (1997), Power et al (2000), Furné et al (2012) and Ashouri et al (2013) have reported an increase in plasma protein of several fish species as a result of starvation. In contrast, some studies on teleosts fish have reported the increased levels of plasma protein in response to food deprivation (Heming & Paleczny 1987;Friedrich & Stepanowska 2001;Polakof et al 2006;Costas et al 2011;Perez-Jimenez et al 2012). Unfortunately, no information regarding plasma albumin and globulin due to starvation is available.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, plasma protein decreased in starved mature carp after five days of starvation (Blasco et al 1992). Pérez-Jiménez et al (2012) reported a significant decline in plasma protein levels of common dentex, Dentex dentex (Linnaeus, 1758), after a five-week starvation.…”
Section: Discussionmentioning
confidence: 95%
“…This enzyme product of this gene functions to link carbohydrate and amino acid metabolism, and increased ALAT activity is connected with enhanced gluconeogenesis and fasting (Méton et al 1999;Fernandez et al 2007;Pérez-Jiménez et al 2012). In fish studied to date, including trout and seabream, one mitochondrial form (mALAT) and two cytosolic isoforms (cALAT1 and cALAT2) have been identified (Méton et al 2004;Fernandez et al 2007;Anaemet et al 2008).…”
Section: Discussionmentioning
confidence: 99%